Lung Collapse during Mini-Thoracotomy Reduces Penetration of Cefuroxime to the Tissue: Interstitial Microdialysis Study in Animal Models - Děrgel, Martin; Voborník, Martin; Pojar, Marek; Karalko, Mikita; Gofus, Jan; Radochová, Věra; Studená, Šárka; Maláková, Jana; Turek, Zdeněk; Chládek, Jaroslav; Manďák, Jiří (Surgical infections, 2021)
Background: Single-lung ventilation facilitates surgical exposure during minimally invasive cardiac surgery. However, a deeper knowledge of antibiotic distribution within a collapsed lung is necessary for effective antibiotic prophylaxis of pneumonia. Patients and Methods: The pharmacokinetics/pharmacodynamics (PK/PD) of cefuroxime were compared between the plasma and interstitial fluid (ISF) of collapsed and ventilated lungs in 10 anesthetized pigs, which were ventilated through a double-lumen endotracheal cannula. Cefuroxime (20 mg/kg) was administered in single 30-minute intravenous infusion. Samples of blood and lung microdialysate were collected until six hours post-dose. Ultrafiltration, in vivo retrodialysis, and high-performance liquid chromatography-tandem mass spectrometry were used to determine plasma and ISF concentrations of free drug. The concentrations were examined with non-compartmental analysis and compartmental modeling. Results: The concentration of free cefuroxime in ISF was lower in the non-ventilated lung than the ventilated one, evidenced by a lung penetration factor of 47% versus 63% (p < 0.05), the ratio between maximum concentrations (65%, p < 0.05), and the ratio between the areas under the concentration-time curve (78%, p = 0.12). The time needed to reach a minimum inhibitory concentration (MIC) was 30%-40% longer for a collapsed lung than for a ventilated one. In addition, a delay of 10-40 minutes was observed for lung ISF compared with plasma. The mean residence time values (ISF collapsed lung > ISF ventilated lung > plasma) could explain the absence of practically important differences in the time interval with the concentration of cefuroxime exceeding the MICs of sensitive strains (≤4 mg/L). Conclusion: The concentration of cefuroxime in the ISF of a collapsed porcine lung is lower than in a ventilated one; furthermore, its equilibration with plasma is delayed. Administration of the first cefuroxime dose earlier or at a higher rate may be warranted, as well as dose intensification of the perioperative prophylaxis of pneumonia caused by pathogens with higher MICs.
Keywords: prasata; Models, Animal; Swine; Pulmonary Atelectasis; atelektáza; minimally invasive cardiothoracic surgery; antibakteriální látky; torakotomie; Microdialysis; lung interstitial microdialysis; mikrodialýza; cefuroxim; Animals; Anti-Bacterial Agents; pharmacokinetics; zvířata; atelectasis; prophylactic antiobiotics; modely u zvířat; Cefuroxime; Thoracotomy; animal study